Identity formation of TEFL graduate students through oral discourse socialization - Ahmadi, Parviz; Abd Samad, Arshad; Noordin, Nooreen (Academy Publisher, 2013)

(untitled)
This paper reports on academic discourse socialization of several EFL teachers in a TEFL graduate program in Iran through oral discourse practices over the first year of the program. It explores how the professional identity of the in-service teachers is affected by the socialization process, their prior histories and contextual factors. It concludes that dialogical interactions through oral discourse practices are likely to result in re-consideration of their prior professional identity. The paper is likely to make a contribution to our understanding of professional identity construction of EFL teachers in graduate programs as far as academic oral discourse practices are concerned.